Graphite negative electrode material and preparation method thereof

By covering the outer layer of silicon carbide with carbon nanotubes, the problem of volume expansion of silicon carbide during charging and discharging is solved, the capacity and stability of graphite negative electrode materials are improved, and the performance of the battery is significantly improved.

CN119650660APending Publication Date: 2025-03-18FUJIAN SHANSHAN TECH CO LTD

Patent Information

Application Number
CN202411928084.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing silicon carbide modification methods have volume expansion problems during charging and discharging, which leads to particles powdering and falling off, affecting the cycle stability of the battery.

Method used

By covering the outer layer of silicon carbide, the expansion deformation of carbon nanotubes is limited, and the carbon nanotube/silicon carbide composite material is prepared.

Benefits of technology

The discharge capacity and stability of artificial graphite negative electrode materials are improved, the risk of silicon carbide pulverization and shedding is reduced, and the energy density and cycling performance of the battery are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a graphite negative electrode material and a preparation method thereof. The invention provides a carbon nano tube / silicon carbide composite material which comprises silicon carbide particles and carbon nano tubes, and the carbon nano tubes are coated on the silicon carbide particles. According to the carbon nano tube / silicon carbide composite material and the carbon nano tube / silicon carbide-graphite matrix composite material disclosed by the invention, a graphite negative electrode material with a stable overall structure and high capacity is obtained by adopting a new coating mode and a new coating process, and the graphite negative electrode material can be used for an artificial graphite negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a graphite negative electrode material and a preparation method thereof. Background Art

[0002] In the field of battery technology, artificial graphite anodes are a widely used battery material. However, artificial graphite still needs to be improved in terms of energy density, cycle life, and charge-discharge rate. To address this issue, researchers have attempted various methods to modify artificial graphite anode materials to improve their performance. Carbon nanotubes, due to their excellent electrical conductivity, mechanical strength, and thermal conductivity, are considered a promising anode material modifier. However, their improvement in anode capacity is limited. Silicon carbide has a much higher capacity limit than graphite, but silicon-based anode materials experience significant volume expansion and contraction during charge and discharge, which can lead to particle pulverization and shedding, thus affecting the battery's cycling stability. Therefore, a new method for synthesizing artificial graphite composites of silicon carbide and carbon nanotubes is needed that can retain the high capacity of silicon carbide while overcoming its susceptibility to expansion, resulting in an artificial graphite anode material with both high capacity and stability.

[0003] CN118524689A: The present invention relates to a honeycomb carbon nanotube / silicon carbide composite material for use in electromagnetic shielding and a preparation method thereof. The preparation method comprises: using 3D printing technology to construct a three-dimensional carbon nanotube cubic framework from a slurry containing carbon nanotubes, a carbon nanotube dispersant, polydimethylsiloxane, and a curing agent; curing the slurry at high temperature to obtain a carbon nanotube / PDMS preform; then using a high-temperature pyrolysis process to pyrolyze PDMS in the resulting preform to obtain a SiC matrix, which is then attached to the carbon nanotubes to produce the carbon nanotube / silicon carbide composite material; wherein the mass ratio of the carbon nanotubes to the polydimethylsiloxane is 1:5 to 1:15; and the high-temperature pyrolysis time is 1 to 50 hours.

[0004] CN118498073A: The present invention relates to the technical field of silicon carbide / carbon nanofiber materials, and provides a carbon nanotube / silicon carbide composite fiber and a preparation method thereof. The method comprises: twisting a carbon nanotube fiber preform to obtain twisted carbon nanotube fibers; homogenizing the twisted carbon nanotube fibers to obtain homogenized carbon nanotube fibers; stretching the homogenized carbon nanotube fibers in the longitudinal direction to obtain carbon nanotube fibers; and depositing a silicon carbide shell layer on the surface of the carbon nanotube fibers to obtain a carbon nanotube / silicon carbide composite fiber. The twisting conditions include a time of 60 seconds to 240 seconds and a twisting speed of 120 rpm to 350 rpm; and the stretching conditions include a stretching force of 5 N to 10 N. The carbon nanotube / silicon carbide composite fiber of the present invention has excellent mechanical, electrical, and thermal properties. Summary of the Invention

[0005] The present invention provides a graphite negative electrode material and a preparation method thereof. In view of the problem of volume expansion still existing in the existing silicon carbide modification method, this patent adopts a new coating method and coating process to obtain an artificial graphite negative electrode with a stable overall structure and high capacity.

[0006] The present invention provides a carbon nanotube / silicon carbide composite material, which comprises silicon carbide particles and carbon nanotubes, wherein the carbon nanotubes are coated on the silicon carbide particles.

[0007] In some embodiments, the coating means that the carbon nanotubes are uniformly arranged on the silicon carbide particles.

[0008] In the present invention, the silicon carbide particles may be conventional silicon carbide particles in the art.

[0009] In some embodiments, the average particle size of the silicon carbide particles is 50-200 nm, preferably 100 nm.

[0010] In the present invention, the carbon nanotubes may be conventional carbon nanotubes in the art.

[0011] In some embodiments, the carbon nanotubes may be multi-arm carbon nanotubes or single-arm carbon nanotubes, preferably single-arm carbon nanotubes.

[0012] In some embodiments, the average particle size of the carbon nanotubes is 1-10 nm, preferably 5 nm.

[0013] In some embodiments, the mass ratio of the silicon carbide particles to the carbon nanotubes is 1:(10-20); preferably 1:10, 1:15, 1:20; more preferably 1:10.

[0014] In some embodiments, the carbon nanotube / silicon carbide composite material consists of silicon carbide particles and carbon nanotubes.

[0015] In some embodiments, the carbon nanotube / silicon carbide composite material consists of 1 part of the silicon carbide particles and 10 parts of the carbon nanotubes, by mass.

[0016] The present invention provides a carbon nanotube / silicon carbide-graphite matrix composite material, which comprises the carbon nanotube / silicon carbide composite material, graphite and a coating agent.

[0017] The graphite may be conventional graphite in the art.

[0018] In some embodiments, the graphite is graphitized petroleum coke or needle coke, such as graphitized petroleum coke.

[0019] In some embodiments, the graphite particle size D50 is ≤16 μm, the discharge capacity is ≥355 mAh / g, and the specific surface area is 0.8-2.0 m 2 / g, moisture ≤0.2%, discharge efficiency ≥91.0%.

[0020] In some embodiments, the mass ratio of the carbon nanotube / silicon carbide composite material to the graphite is (0.5-1):(100-69), for example, 1:84.

[0021] In some embodiments, the coating agent may be modified asphalt; preferably, the coking value is ≤30% and the density is 1.05-1.1 g / cm at 30°C. 3 modified asphalt.

[0022] In some embodiments, the mass ratio of the coating agent to the graphite is (5-30):(100-69), for example, 15:84.

[0023] In some embodiments, the mass ratio of the coating agent to the carbon nanotube / silicon carbide composite material is (5-30):(0.5-1); for example, 15:1.

[0024] In some embodiments, the mass ratio of the carbon nanotube / silicon carbide composite material, the graphite, and the coating agent is (0.5-1):(100-69):(5-30), for example, 1:84:15.

[0025] In some embodiments, the carbon nanotube / silicon carbide-graphite matrix composite material has a first efficiency of 91-95.5%, for example 95.5%.

[0026] In some embodiments, the carbon nanotube / silicon carbide-graphite matrix composite material is composed, by mass, of 1 part of the carbon nanotube / silicon carbide composite material, 84 parts of the graphitized petroleum coke, and 15 parts of the modified asphalt.

[0027] The present invention also provides a method for preparing a carbon nanotube / silicon carbide composite material, which comprises the following steps:

[0028] A mixture of silicon carbide particles, carbon nanotubes and a catalyst is heat-treated to obtain the carbon nanotube / silicon carbide composite material; the mass ratio of the silicon carbide particles to the carbon nanotubes is 1:(10-20).

[0029] In some embodiments, the average particle size of the silicon carbide particles is 50-200 nm, preferably 100 nm.

[0030] In some embodiments, the carbon nanotubes have a particle size of 1-10 nm, preferably 5 nm, and more preferably are single-arm carbon nanotubes with a particle size of 5 nm.

[0031] In some embodiments, the catalyst is ferrocene.

[0032] In some embodiments, the mass ratio of the silicon carbide particles to the carbon nanotubes is 1:10, 1:15, or 1:20; more preferably 1:10.

[0033] In some embodiments, the heat treatment vessel for the mixture is a muffle furnace.

[0034] In some embodiments, a hydrogen-argon mixed gas is introduced during the heat treatment of the mixture; the hydrogen-argon mixed gas is preferably a hydrogen-argon mixed gas containing 4% hydrogen.

[0035] In some embodiments, the heat treatment is performed by raising the temperature to 750-850°C, preferably 800°C.

[0036] In some embodiments, the heating rate of the heat treatment is 10°C / min.

[0037] In some embodiments, the heat treatment is followed by a 20-hour incubation.

[0038] In some embodiments, the method for preparing the carbon nanotube / silicon carbide composite material further comprises cleaning, wherein the cleaning comprises treating the carbon nanotubes with concentrated nitric acid under ultrasonic conditions.

[0039] The present invention also provides a method for preparing a carbon nanotube / silicon carbide-graphite matrix composite material, which comprises the following steps:

[0040] S1: mixing the coating agent, the carbon nanotube / silicon carbide composite material and graphite to obtain material A;

[0041] S2: Carbonizing material A at high temperature to obtain a graphite negative electrode material.

[0042] In some embodiments, the coating agent may be modified asphalt, preferably with a coking value of ≤30% and a density of 1.05-1.1 g / cm at 30°C. 3 modified asphalt.

[0043] In some embodiments, the graphite may be graphitized petroleum coke, preferably with a particle size D50 of ≤16㎛, a discharge capacity of ≥355mAh / g, and a specific surface area of ​​0.8-2.0m 2 / g, moisture ≤ 0.2%, and discharge efficiency ≥ 91.0% of graphitized petroleum coke.

[0044] In some embodiments, the mass ratio of the material A to the graphite to the coating agent is (0.5-1):(100-69):(5-30), preferably 1:84:15.

[0045] In some embodiments, the mixing container is a horizontal ribbon mixer; the rotating speed of the mixing container is 400-800 r / min, for example, 600 r / min.

[0046] In some embodiments, the high-temperature carbonization container is a roller hearth furnace; preferably, a six-row double-layer nitrogen roller hearth furnace.

[0047] In some embodiments, the heating rate of the high-temperature carbonization is 4-6°C / min, preferably 5°C / min.

[0048] In some embodiments, the temperature of the high-temperature carbonization is 900-1200° C., preferably 1000° C.; the holding time of the high-temperature carbonization is 2-10 h, preferably 10 h.

[0049] In some embodiments, an inert atmosphere is used for protection during the high-temperature carbonization. The inert atmosphere may be a nitrogen or argon atmosphere; preferably a nitrogen atmosphere; and the gas flow rate of the inert atmosphere is 2 L / h-20 L / h.

[0050] In some embodiments, the high-temperature carbonization is controlled by a heating curve, and the specific surface area and coating effect are controlled by controlling the length of time of heating from room temperature (25°C) to 900-1200°C.

[0051] A graphite negative electrode material is prepared by using the above raw materials through the above preparation method.

[0052] The advantages of the present invention are that by coating the outer layer of silicon carbide with high-strength carbon nanotubes, the expansion and deformation of silicon carbide is limited. Simultaneously, the high capacity of silicon carbide and the high strength and high-temperature resistance of carbon nanotubes are combined to effectively improve the discharge capacity and stability of the finished artificial graphite negative electrode material, reduce the risk of silicon carbide pulverization and shedding, and improve the capacity and life of the battery. Furthermore, the method is simple to operate, easy to implement, and can be used for industrial production.

[0053] Experimental results show that the capacity of the graphite negative electrode material treated by the modification method of the present invention can be increased by more than 20% under high-rate charge and discharge conditions depending on the ratio of silicon carbide to carbon nanotubes added, significantly improving the energy density and cycle performance of the battery. DETAILED DESCRIPTION

[0054] The present invention is further illustrated by way of examples below, but the present invention is not limited to the scope of the examples. Experimental methods in the following examples where specific conditions are not specified were performed according to conventional methods and conditions, or selected according to the product specifications.

[0055] The present invention is described in detail below with reference to specific embodiments. In the present invention, the graphitized petroleum coke is a semi-finished product of artificial graphite, characterized by: particle size D50: ≤16㎛, discharge capacity ≥355mAh / g, specific surface area 0.8-2.0m 2 / g, moisture ≤0.2%, discharge efficiency ≥91.0%.

[0056] Example 1:

[0057] A graphite negative electrode material composed of carbon nanotube-coated silicon carbide and composite artificial graphite, the main preparation steps of which are as follows:

[0058] (1) Take silicon carbide with a particle size of 100 nm and single-walled carbon nanotubes with a size of 5 nm. Treat the carbon nanotubes with concentrated nitric acid under ultrasonic conditions and dry them in a vacuum oven at a temperature of 80-120°C for 24 hours.

[0059] (2) Silicon carbide particles were placed in a mixed solution containing ferrocene and carbon nanotubes (silicon carbide: carbon nanotubes = 1:10), placed in a muffle furnace, and passed through a hydrogen-argon (4% hydrogen) mixed gas. The temperature was raised to 800°C at a heating rate of 10°C / min and kept at this temperature for 20 hours to obtain material A.

[0060] (3) Material A was collected, and graphitized petroleum coke B with a particle size D50: ≤16㎛ and an asphalt coating agent C with a coking value of 30% were added into a horizontal ribbon mixer at a ratio of A:B:C = 1:84:15 and blended at 600 r / min to obtain material D;

[0061] (4) Collect material D and send it to the roller kiln (six-row double-layer nitrogen roller kiln), N 2 Protection, carbonization temperature is 1000 ℃, and carbonization time is 24h to obtain the negative electrode material of carbon nanotube-coated silicon carbide composite artificial graphite.

[0062] Example 2:

[0063] A graphite negative electrode material composed of carbon nanotube-coated silicon carbide and composite artificial graphite, the main preparation steps of which are as follows:

[0064] (1) Take silicon carbide with a particle size of 100 nm and single-walled carbon nanotubes with a size of 5 nm. Treat the carbon nanotubes with concentrated nitric acid under ultrasonic conditions and dry them in a vacuum oven at a temperature of 80-120°C for 24 hours.

[0065] (2) Silicon carbide particles were placed in a mixed solution containing ferrocene and carbon nanotubes (silicon carbide: carbon nanotubes = 1:10), placed in a muffle furnace, and passed through a hydrogen-argon mixture. The temperature was raised to 800°C at a heating rate of 10°C / min and kept at this temperature for 20 hours to obtain material A.

[0066] (3) Material A was collected, and graphitized petroleum coke B with a particle size D50: ≤16㎛ and an asphalt coating agent C with a coking value of 30% were added into a horizontal ribbon mixer at a ratio of A:B:C = 0.5:85:14.5 and blended at 600 r / min to obtain material D;

[0067] (4) Collect material D and send it to a roller kiln for carbonization under N2 protection at a carbonization temperature of 1000°C and a carbonization time of 24 hours to obtain a negative electrode material of carbon nanotube-coated silicon carbide composite artificial graphite.

[0068] Example 3:

[0069] A graphite negative electrode material composed of carbon nanotube-coated silicon carbide and composite artificial graphite, the main preparation steps of which are as follows:

[0070] (1) Take silicon carbide with a particle size of 100 nm and single-walled carbon nanotubes with a size of 15 nm. Treat the carbon nanotubes with concentrated nitric acid under ultrasonic conditions and dry them in a vacuum oven at a temperature of 80-120°C for 24 hours.

[0071] (2) Silicon carbide particles were placed in a mixed solution containing ferrocene and carbon nanotubes (silicon carbide: carbon nanotubes = 1:10), placed in a muffle furnace, and passed through a hydrogen-argon mixture. The temperature was raised to 800°C at a heating rate of 10°C / min and kept at this temperature for 20 hours to obtain material A.

[0072] (3) Material A was collected, and graphitized petroleum coke B with a particle size D50: ≤16㎛ and an asphalt coating agent C with a coking value of 30% were added into a horizontal ribbon mixer at a ratio of A:B:C = 1:85:14 and blended at 600 r / min to obtain material D.

[0073] (4) Collect material D and send it to a roller kiln for carbonization under N2 protection at a carbonization temperature of 1000°C and a carbonization time of 24 hours to obtain a negative electrode material of carbon nanotube-coated silicon carbide composite artificial graphite.

[0074] Example 4:

[0075] A graphite negative electrode material composed of carbon nanotube-coated silicon carbide and composite artificial graphite, the main preparation steps of which are as follows:

[0076] (1) Take silicon carbide with a particle size of 100 nm and single-walled carbon nanotubes with a size of 5 nm. Treat the carbon nanotubes with concentrated nitric acid under ultrasonic conditions and dry them in a vacuum oven at a temperature of 80-120°C for 24 hours.

[0077] (2) Silicon carbide particles were placed in a mixed solution containing ferrocene and carbon nanotubes (silicon carbide: carbon nanotubes = 1:15), placed in a muffle furnace, and passed through a hydrogen-argon mixture. The temperature was raised to 800°C at a heating rate of 10°C / min and kept at this temperature for 20 hours to obtain material A.

[0078] (3) Material A was collected, and graphitized petroleum coke B with a particle size D50: ≤16㎛ and an asphalt coating agent C with a coking value of 30% were added into a horizontal ribbon mixer at a ratio of A:B:C = 1:85:14 and blended at 600 r / min to obtain material D.

[0079] (4) Collect material D and send it to a roller kiln for carbonization under N2 protection at a carbonization temperature of 1000°C and a carbonization time of 20 hours to obtain a negative electrode material of carbon nanotube-coated silicon carbide composite artificial graphite.

[0080] Example 5:

[0081] A graphite negative electrode material composed of carbon nanotube-coated silicon carbide and composite artificial graphite, the main preparation steps of which are as follows:

[0082] (1) Take silicon carbide with a particle size of 100 nm and single-walled carbon nanotubes with a size of 5 nm. Treat the carbon nanotubes with concentrated nitric acid under ultrasonic conditions and dry them in a vacuum oven at a temperature of 80-120°C for 24 hours.

[0083] (2) Silicon carbide particles were placed in a mixed solution containing ferrocene and carbon nanotubes (silicon carbide: carbon nanotubes = 1:20), placed in a muffle furnace, and passed through a hydrogen-argon mixture. The temperature was raised to 800°C at a heating rate of 20°C / min and kept at this temperature for 20 hours to obtain material A.

[0084] (3) Material A was collected, and graphitized petroleum coke B with a particle size D50: ≤16㎛ and an asphalt coating agent C with a coking value of 30% were added into a horizontal ribbon mixer at a ratio of A:B:C=1:85:14 and blended at 600r / min to obtain material D.

[0085] (4) Collect material D and send it to a roller kiln for carbonization under N2 protection at a carbonization temperature of 1000°C and a carbonization time of 24 hours to obtain a negative electrode material of carbon nanotube-coated silicon carbide composite artificial graphite.

[0086] Comparative Example 1:

[0087] A graphite negative electrode material of carbon nanotube composite artificial graphite, the main preparation steps of which are as follows:

[0088] (1) Take single-walled carbon nanotubes A with a size of 5 nm, graphitized petroleum coke B with a particle size D50: ≤16㎛ and asphalt coating agent C with a coking value of 30% at a ratio of A:B:C=1:94:5, add them into a horizontal ribbon mixer at 600 r / min and mix them to obtain material D;

[0089] (2) Collect material D and send it to a roller kiln for carbonization under N2 protection at a carbonization temperature of 1000°C and a carbonization time of 24 hours to obtain a negative electrode material of carbon nanotube composite artificial graphite.

[0090] The test method is as follows:

[0091]

[0092] The test results of the materials obtained in each embodiment and comparative example are shown in the following table:

[0093]

[0094] Looking at the five examples and Comparative Example 1, Comparative Example 1, which only incorporates carbon nanotubes, exhibits significantly lower discharge capacity compared to the examples incorporating silicon carbide-carbon nanotubes of varying sizes and ratios. Furthermore, the discharge capacity of Comparative Example 1 approaches the limit of artificial graphite, whereas the addition of silicon carbide to a carbon nanotube-coated silicon carbide composite artificial graphite negative electrode material overcomes this limitation.

Claims

1. A carbon nanotube / silicon carbide composite material, comprising silicon carbide particles and carbon nanotubes, wherein the carbon nanotubes are coated on the silicon carbide particles.

2. The carbon nanotube / silicon carbide composite material according to claim 1, characterized in that: One or more of the following conditions are met: (1) The average particle size of the silicon carbide particles is 50-200 nm, preferably 100 nm; (2) The carbon nanotubes are multi-arm carbon nanotubes or single-arm carbon nanotubes, preferably single-arm carbon nanotubes; (3) The average particle size of the carbon nanotubes is 1-10 nm, preferably 5 nm; (4) The mass ratio of the silicon carbide particles to the carbon nanotubes is 1:(10-20); preferably 1:10, 1:15, 1:20; more preferably 1:10; (5) The carbon nanotube / silicon carbide composite material consists of silicon carbide particles and carbon nanotubes; (6) The coating is that the carbon nanotubes are uniformly arranged on the silicon carbide particles.

3. The carbon nanotube / silicon carbide composite material according to claim 2, characterized in that: In terms of mass, it consists of 1 part of the silicon carbide particles and 10 parts of the carbon nanotubes.

4. A carbon nanotube / silicon carbide-graphite matrix composite material, comprising the carbon nanotube / silicon carbide composite material according to any one of claims 1 to 3, graphite and a coating agent.

5. The carbon nanotube / silicon carbide-graphite matrix composite material according to claim 4, characterized in that: It meets one or more of the following conditions: (1) The graphite is graphitized petroleum coke or needle coke, such as graphitized petroleum coke; (2) The graphite has a particle size D50 ≤ 16 μm, a discharge capacity ≥ 355 mAh / g, a specific surface area of ​​0.8-2.0 m2 / g, a moisture content ≤ 0.2%, and a discharge efficiency ≥ 91.0%; (3) The mass ratio of the carbon nanotube / silicon carbide composite material to the graphite is (0.5-1):(100-69), for example, 1:84; (4) The coating agent is modified asphalt; preferably, the coking value is ≤30% and the density is 1.05-1.1 g / cm at 30°C 3 Modified asphalt; (5) The mass ratio of the coating agent to the graphite is (5-30):(100-69), for example, 15:84; (6) The mass ratio of the coating agent to the carbon nanotube / silicon carbide composite material is (5-30):(0.5-1); for example, 15:1; (7) The mass ratio of the carbon nanotube / silicon carbide composite material, the graphite and the coating agent is (0.5-1):(100-69):(5-30), for example, 1:84:15; (8) The first efficiency of the carbon nanotube / silicon carbide-graphite matrix composite material is 91-95.5%, for example 95.5%; Preferably, the carbon nanotube / silicon carbide-graphite matrix composite material is composed, by weight, of 1 part of the carbon nanotube / silicon carbide composite material, 84 parts of the graphitized petroleum coke and 15 parts of the modified asphalt.

6. A method for preparing the carbon nanotube / silicon carbide composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The mixture of silicon carbide particles, carbon nanotubes and a catalyst is heat-treated to obtain the carbon nanotube / silicon carbide composite material; the mass ratio of the silicon carbide particles to the carbon nanotubes is 1:(10-20).

7. The method for preparing the carbon nanotube / silicon carbide composite material according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The average particle size of the silicon carbide particles is 50-200 nm, preferably 100 nm; (2) The particle size of the carbon nanotube is 1-10 nm; preferably 5 nm; more preferably a single-arm carbon nanotube with a particle size of 5 nm; (3) The catalyst is ferrocene; (4) The mass ratio of the silicon carbide particles to the carbon nanotubes is 1:10, 1:15, 1:20; more preferably 1:10; (5) The heat treatment container of the mixture is a muffle furnace; (6) introducing a hydrogen-argon mixed gas during the heat treatment of the mixture; the hydrogen-argon mixed gas is preferably a hydrogen-argon mixed gas containing 4% hydrogen; (7) The heat treatment is performed by heating the temperature to 750-850°C, preferably 800°C; (8) The heating rate of the heat treatment is 10°C / min; (9) keeping the heat for 20 hours after the heat treatment; (10) The method for preparing the carbon nanotube / silicon carbide composite material further comprises cleaning, wherein the cleaning refers to treating the carbon nanotubes with concentrated nitric acid under ultrasonic conditions.

8. A method for preparing the carbon nanotube / silicon carbide-graphite matrix composite material according to any one of claims 4 to 5, comprising the following steps: S1: the carbon nanotube / silicon carbide composite material, the coating agent and graphite are mixed to obtain material A; S2: Carbonizing material A at high temperature to obtain a graphite negative electrode material.

9. The method for preparing the carbon nanotube / silicon carbide-graphite matrix composite material according to claim 8, characterized in that: It meets one or more of the following conditions: (1) The coating agent is modified asphalt, preferably with a coking value of ≤30% and a density of 1.05-1.1 g / cm at 30°C. 3 Modified asphalt; (2) The graphite is graphitized petroleum coke, preferably with a particle size D50 of ≤16㎛, a discharge capacity of ≥355mAh / g, and a specific surface area of ​​0.8-2.0m 2 / g, water content ≤ 0.2%, and graphitized petroleum coke with a discharge efficiency ≥ 91.0%; (3) The mass ratio of the material A to the graphite to the coating agent is (0.5-1):(100-69):(5-30), preferably 1:84:15; (4) The mixing container is a horizontal ribbon mixer; the rotating speed of the mixing container is 400-800 r / min, for example, 600 r / min; (5) The high-temperature carbonization container is a roller hearth kiln; preferably a six-row double-layer nitrogen roller hearth furnace; (6) The heating rate of the high temperature carbonization is 4-6°C / min, preferably 5°C / min; (7) The temperature of the high-temperature carbonization is 900-1200°C, preferably 1000°C; the holding time of the high-temperature carbonization is 2-10h, preferably 10h; (8) During the high-temperature carbonization, an inert atmosphere is used for protection, and the inert atmosphere is a nitrogen or argon atmosphere; preferably a nitrogen atmosphere; the gas flow rate of the inert atmosphere is 2L / h-20L / h; (9) The high temperature carbonization is controlled by a heating curve, and the length of time for heating from room temperature (25°C) to 900-1200°C is controlled to control the specific surface area and coating effect.

10. A graphite negative electrode material, comprising the carbon nanotube / silicon carbide composite material according to any one of claims 1 to 3 or the carbon nanotube / silicon carbide-graphite matrix composite material according to any one of claims 4 to 5.

Citation Information

Patent Citations

  • Carbon nanotube / silicon carbide composite fiber and preparation method thereof

    CN118498073A

Cited By

  • Negative active material and preparation method thereof, negative pole piece and lithium ion battery

    CN121460530A